HUMAN RIGHTS IN NATIONAL CYBERSECURITY STRATEGY DOCUMENTS - ÜNVER, Gül Nazik (Cyberpolitik Journal, 2017)
In this paper, the United States, Turkey, United Kingdom, Germany, the Netherlands and Belgium's national cyber security strategy documents and their impact on human rights and international human rights protection mechanisms are being analyzed in the cyber space. First of all, this work will focus on steps and suggestions with a new outlook for bringing a different dimension by focusing on legal regulations of countries, the security approaches of countries by putting forward the perspective of national cyber security. In particular, the paper describes security and strategic management tasks. To clarify the context of the legal approach to a specific nation's cyber security, it presents a literatute review of the objectives of the national information society and the national cyber security strategy.